(untitled) (Altre Modernità, 2011)
Miriam Clavir, Preserving What is Valued: Museums, Conservation, and First Nations (UBC Press, Vancouver, 2002, 295 pp., ISBN 0-7748-0860-8 e 0-7748-0861-6) di Claudia Gualtieri